2016
DOI: 10.1186/s12889-016-3057-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a United Kingdom-wide campaign to tackle antimicrobial resistance on self-reported knowledge and behaviour change

Abstract: BackgroundAs part of the 2014 European Antibiotic Awareness Day plans, a new campaign called Antibiotic Guardian (AG) was launched in the United Kingdom, including an online pledge system to increase commitment from healthcare professionals and members of the public to reduce antimicrobial resistance (AMR). The aim of this evaluation was to determine the impact of the campaign on self-reported knowledge and behaviour around AMR.MethodsAn online survey was sent to 9016 Antibiotic Guardians (AGs) to assess chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 45 publications
3
57
0
Order By: Relevance
“…Antibiotic use for adults diagnosed with ARTI can be reduced using a combination of PCP and patient educational interventions [ 85 , 86 , 96 , 97 ]. One such campaign based in Britain, Antibiotic Guardian, increased commitment to tackling AMR in both PCPs and members of the public, increased self-reported knowledge and changed self-reported behaviour particularly among people with prior AMR awareness [ 98 ]. In paediatric practice, a systematic review concluded that educational interventions targeting clinicians and parents of affected children are more effective than those for either group alone, and the most effective strategies address patient–clinician communication [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotic use for adults diagnosed with ARTI can be reduced using a combination of PCP and patient educational interventions [ 85 , 86 , 96 , 97 ]. One such campaign based in Britain, Antibiotic Guardian, increased commitment to tackling AMR in both PCPs and members of the public, increased self-reported knowledge and changed self-reported behaviour particularly among people with prior AMR awareness [ 98 ]. In paediatric practice, a systematic review concluded that educational interventions targeting clinicians and parents of affected children are more effective than those for either group alone, and the most effective strategies address patient–clinician communication [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nationwide antibiotic restriction policies or campaigns were effective in the UK, France, Belgium, the Netherlands, and Italy [ 21 , 37 , 38 ], except that despite reduced antibiotic consumption in Italy, awareness of antibiotic resistance had not increased [ 37 ]. Spain has conducted a campaign since 2006 and reduced antibiotic consumption, but many antibiotics are still sold without a prescription in some areas [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of Antibiotic Guardian found that it effectively raised awareness of antimicrobial resistance/stewardship [18] and so should continue to be widely promoted. AMS leads reported that some GP practices display signed posters of their prescribers' Antibiotic Guardian pledges for patients to see.…”
Section: Discussionmentioning
confidence: 99%